Pengaruh Pendekatan Saintifik Terhadap Keterampilan Berpikir Kritis Siswa - Baiq Azmi Sukroyanti; Ika Sufianti (Universitas Pendidikan Mandalika, 2017)
[Title: The Effect of Scientific Approaches Toward Students' Critical Thinking Skills]. This study aims to determine the influence of scientific approach toward the critical thinking skills of students. Indicator of critical thinking skills provides a simple explanation, build skills, conclude, provide further explanation, and set the strategies an tactics. Design in this study was quasi-experimental with posttest only control group design. The population of the study was all of the students class VII SMPN 16 Mataram. The samples of the study consist of two class, that was experiment and control, which is experiment class was taught using scientific approach and control class was taught using conventional methods. The instrument of the study was a description test of critical thinking skill. Data postest show the average of creative thinking skill in the experimental class is 72,32% categorized well while for the control class is equal to 62,67% categorized quite well. The analysis data found tcount 3,28 and ttable 1,67 (the significant level of 5%). The result shows that there was an effect of a scientific approach toward critical thinking skills of the students in vibration and waves material.